The mechanical and histochemical characteristics of an in vivo nerve-muscle preparation of normal and dystrophic avian muscle : effects of sex, disease and age - Howlett, Susan E., 1957- (1982)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1982. Medicine Bibliography: leaves 171-182. An in vivo nerve-muscle preparation of the posterior latissimus dorsi muscle (PLD) has been used extensively to study contractile, pharmacological and electrophysiological characteristics of avian muscles affected by hereditary muscular dystrophy. The use of the preparation is limited since there is no convenient artery for cannulation to assess the acute effects of substances of potential therapeutic value. A preparation that appears to meet this requirement, the extensor digitorum communis (EDC) muscle preparation, is developed in the present study. The mechanical and histochemical characteristics of the EDC muscle compare favorably to those reported for normal and dystrophic avian muscle in the PLD preparation. -- The gene for muscular dystrophy in chickens is thought to be autosomal recessive but personal observations and communications with some workers in the area suggest that the gene is expressed differently in males and females. The mechanical characteristics of the EDC muscle have been examined in old and young groups (old = greater than 6 months; young = 6-9 weeks) of normal and dystrophic chickens with respect to sex. Results showed that age-related sex differences were apparent for mechanical parameters known to distinguish normal and cystrophic birds, that is ability to rise from the supine position, wing apposition score, post-tetanic potentiation, twitch-tetanus ratio and post-tetanic contracture. The sex differences observed in young birds indicate that the females were more severely affected by the disease than were the males. In the older birds the contractile responses of the EDC in males showed classic signs of dystrophy while females were often not significantly different from normal. If the inheritance pattern is truly autosomal recessive then perhaps there is an endogenous "protective" factor in the mature female. It is suggested that the lowered plasma cholesterol in the egg laying hen could account for the observed sex differences. Defects have been reported in a variety of membranes in human and animal muscular dystrophies. Since cholesterol is known to decrease membrane fluidity and since increases in plasma cholesterol have been reported in dystrophic chickens, a dramatic decrease in plasma cholesterol could perhaps improve the dystrophic condition.